A teia de poder: o coronel Junqueira e a política da Primeira Republica Ribeirão Preto de 1889-1932 - Mattioli, Alexandre Ferreira (2014)
This study aimed to analyze the political career of Colonel Joaquim da Cunha Diniz Junqueira. Thus, were developed a research on the construction of its web of power, through which exerted a strong political influence in the state of São Paulo, especially in the region of Ribeirão Preto, also often impacting the state policy and federal. Thereby, was br7iefly analyzed the formation of the Ribeirão Preto city and also the powerful family Junqueira, especially regarding their strategies for obtaining and maintaining power. In this context, were discussed aspects of the acting of the colonels and colonel Junqueira during relevant moments in the history of the First Republic, as the Lieutenants\' Revolt and the Constitutional Revolution of 1932. This was possible through information gathering of the private collection of Colonel Junqueira and other important politicians of the First Republic - as the governor of the state of São Paulo Altino Arantes and the president Luiz Washington - as well as newspapers, minutes of the Municipality of Ribeirão Preto and several other sources. Also were investigated to improve this work several elements of the political culture of the state of São Paulo, particularly between the years 1887 and 1932.